2012
DOI: 10.2131/jts.37.675
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress in the testis induced by tamoxifen and its effects on early embryo development in isogenic mice

Abstract: -Oxidative stress induced by tamoxifen (TAM) in male testis and its effects on fertility and early embryo development were investigated. TAM was orally administered for 4 weeks repeatedly to two isogenic male mice strains, inbred strain of C57BL/6J (B6) mice and hybrid strain of C57BL/6J x CBA F1 (B6CBAF1) mice. Oxidative stress in mice testis was measured based on the level of lipid peroxidation (LPO). The LPO level was significantly increased in inbred strain of B6 mice (p < 0.05), but not hybrid strain of B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…In the process of cancer treatment, many antitumor drugs usually produce some adverse effects, which will affect further clinical therapies. For example, the widely used chemotherapeutic drugs doxorubicin (DOX), cisplatin (CIS), Fluorouracil (5-FU), methotrexate (MTX) and tamoxifen (TAM) have high antitumor efficacy, meanwhile with serious damage to multiple organs (e.g., cardiomyopathy, acute renal failure, acute toxic leukoencephalopathy, hepatic steatosis and testicular toxicity) (154)(155)(156)(157)(158). For male reproduction, these chemotherapy drugs cause damage to male reproductive function in different degrees, such as testicular toxicity (decreased testicular weight, sperm count, plasma T and testicular histopathological changes) and genetic toxicity (chromosomal aberrations).…”
Section: Antitumor Agentsmentioning
confidence: 99%
“…In the process of cancer treatment, many antitumor drugs usually produce some adverse effects, which will affect further clinical therapies. For example, the widely used chemotherapeutic drugs doxorubicin (DOX), cisplatin (CIS), Fluorouracil (5-FU), methotrexate (MTX) and tamoxifen (TAM) have high antitumor efficacy, meanwhile with serious damage to multiple organs (e.g., cardiomyopathy, acute renal failure, acute toxic leukoencephalopathy, hepatic steatosis and testicular toxicity) (154)(155)(156)(157)(158). For male reproduction, these chemotherapy drugs cause damage to male reproductive function in different degrees, such as testicular toxicity (decreased testicular weight, sperm count, plasma T and testicular histopathological changes) and genetic toxicity (chromosomal aberrations).…”
Section: Antitumor Agentsmentioning
confidence: 99%
“…[58] In contrast to these findings, it has been reported that TAM increased lipid peroxidation in B6, but not in B6CBAF1. [59] It has also been reported that raloxifene protected striatal dopaminergic neurons against 6-hydroxydopamine-induced neurotoxicity in the rat. The effect was accompanied by a significant recovery in behavior tests, significant attenuation of neuronal apoptosis and oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…TAM is also reported to induce symplast, distort seminiferous tubules, and geminal epithelial sloughing in rat testis (D’Souza, 2003). Furthermore, oxidative stress induced by TAM significantly reduce the fertilization rate of B6 mice (Lee et al., 2012; Pagano et al, 2001) causing alterations that are harmful to male fertility. TAM‐associated toxicities in the management of breast cancer are tricky for its practical usefulness.…”
Section: Introductionmentioning
confidence: 99%